Valproate-Induced Malformations - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Two children born with birth defects after intrauterine exposure to valproic acid are reported from the Dept Pediatrics Hopital Sainte-Justine, University of Montreal, Quebec, Canada.